Design and fabrication of large polymer constructions in space - Kondyurin, A. V. (Elsevier, 2023)
Design and Fabrication of Large Polymer Constructions in Space is a ground-breaking study of the polymeric materials, advanced chemical processes, and cutting-edge technology required in the construction of large polymer-based structures for space, when all steps in the process are carried out in the space environment, whether in orbit, in deep space, or on the surface of a moon, asteroid, or planet. The book begins by introducing the fundamentals and requirements of large constructions and inflatable structures for space. The next section of the book focuses on the utilization of polymeric materials within the space environment, examining the effects on materials (vacuum, plasma, temperature), the possible approaches to polymerization both in space and in orbit, the preparation and structure of polymer composites, and the methods for testing materials and structures in terms of strength, defects, and aging. Three chapters then cover how these materials and techniques might be applied to specific categories of construction, including larger space habitats, supporting space structures, and ground infrastructure. Finally, the financial aspects, the consequences for human space exploitation, and the possible future developments are discussed. Using materials science to push the boundaries of construction for space exploration and exploitation, this book is a unique resource for academic researchers and advanced students across polymer science, advanced materials, chemical engineering, construction, and space engineering, as well as for researchers, scientists and engineers at space agencies, companies and laboratories, involved in developing materials or technology for use in space. This is also of great interest to anyone interested in the role of materials science in the building of large space stations, spacecraft, planetary bases, large aperture antenna, radiation and thermal shields, and repairmen sets.